Miniature fixed-point cells for self-calibration of type C high-temperature thermocouples. (21st October 2019) - Sun, J P; Pan, J; Lu, X F; Manoi, A; Zhang, T T
Abstract: A high-temperature tungsten-rhenium (W-Re) thermocouple is commonly used at temperatures up to 2000 °C for the high melting temperature of the thermoelement materials. When exposed to high temperatures, a thermocouple can show significant thermoelectric drift, which increases measurement uncertainty. The uncontrolled drift may come from the change in the crystallographic structure, oxidization of the thermoelement materials, interaction between the thermoelement materials and insulator materials and some other unknown reasons. Therefore, periodic recalibration of the thermocouple should be performed; however, sometimes it is not possible to remove the sensor out of the process, especially in some special fields, such as a nuclear power plant. Self-validation methods for thermocouples provide a solution to avoid this drawback. In this paper, miniature eutectic fixed-point cells are presented for self-validation of W-Re thermocouples. To prevent the breakage of the graphite crucible, these cylindrical miniature fixed-point cells contain several small independent crucibles and one thermocouple well, which increase the robustness of the miniature cell. The melting temperature was assigned by a radiation thermometer traced to the primary radiation standard at NIM. The effect of the temperature offset and temperature ramping rate on the melting temperature were checked. The performance of the miniature fixed-point cells and type C thermocouple, including characterization of the stability and repeatability, is presented.